On Almost α,θρ-Contractions on Quasimetric Space and Their Fixed Points - Gonca Durmaz Güngör; Seda Üçüncüoğlu; Murat Olgun; Ishak Altun (Journal of Mathematics)
In this paper, we introduce the concept of almost α,θρ-contraction mappings on quasimetric spaces. Then, under certain conditions, we present some fixed-point results for almost α,θρ-contraction mappings with respect to ω and γ on both left K-complete and left M-complete quasimetric spaces.